STH-net: a soil monitoring network for process-based hydrological modelling from the pedon to the hillslope scale - Martini, Edoardo; Bauckholt, Matteo; Kögler, Simon; Kreck, Manuel; Roth, Kurt; Werban, Ulrike; Wollschläger, Ute; Zacharias, Steffen (Earth system science data, 2021)
Abstract.The Schäfertal Hillslope site is part of the TERENO Harz/Central German Lowland Observatory, and its soil water dynamics are being monitored intensively as part of an integrated, long-term, multi-scale, and multi-temporal research framework linking hydrological, pedological, atmospheric, and biodiversity-related research to investigate the influences of climate and land use change on the terrestrial system. Here, a new soil monitoring network, indicated as STH-net, has been recently implemented to provide high-resolution data about the most relevant hydrological variables and local soil properties. The monitoring network is spatially optimized, based on previous knowledge from soil mapping and soil moisture monitoring, in order to capture the spatial variability in soil properties and soil water dynamics along a catena across the site as well as in depth. The STH-net comprises eight stations instrumented with time-domain reflectometry (TDR) probes, soil temperature probes, and monitoring wells. Furthermore, a weather station provides data about the meteorological variables. A detailed soil characterization exists for locations where the TDR probes are installed. All data have been measured at a 10 min interval since 1 January 2019. The STH-net is intended to provide scientists with data needed for developing and testing modelling approaches in the context of vadose-zone hydrology at spatial scales ranging from the pedon to the hillslope. The data are available from the EUDAT portal (https://doi.org/10.23728/b2share.82818db7be054f5eb921d386a0bcaa74, Martini et al., 2020).
Gesehen am 02.08.2021